Terorisme Dan Migrasi Internasional: Dampak Dan Tantangan Bagi Indonesia - Sugiyono, Arief Febriansyah; Rivando, Boy; Kurniawan, Rizky; Bayuaji, Werdy Satrio; Martin S, Yosia (UI Scholars Hub, 2022)
Movement of people that are cross-border or international migration is a global phenomenon whose frequency is increasing from year to year because it is driven by developments in the current global situation. The presence of migrants and/or refugees can bring new threats to state security and sovereignty. Threats that not only contribute to the emergence of transnational crime but are more complex in relation to other threats such as environmental degradation, the development of religious radicalism, sectarianism and others which are increasingly undermining the existence of a nation and state. The phenomenon of illegal immigrants connected to terrorism has been around for a long time. Illegal immigrants can become terrorists and terrorists can become immigrants. The current problem of terrorism is not only a problem for each country but has become an international problem. Terrorism has become a common enemy because it is a serious crime because it is contrary to human values. Of course, this is a challenge for the global community, which requires the involvement of many parties to handle it, given the problems that arise are very complex and multidimensional. Keywords : Terrorism, Migration, International Migration